An ecological perspective in the evolutionary theology - Grygiel, Wojciech P. (Studia Philosophiae Christianae, 2020)
A new paradigm in theology, termed evolutionary theology, supports the understanding of ecology as the proper ordering of the relations between living organisms and their environment. It is argued that evolutionary theology yields a unique conceptual framework in which the human species share a common history with the entire Universe and respecting nature’s integrity means securing a common destiny to everything that exists. This is a powerful motivation for adopting a balanced ecological attitude aimed at respecting nature’s inherent integrity. Furthermore, proposing theological arguments to substantiate ecological claims will help neutralize the objections that religion as such promotes anti-ecological attitudes. Such objections become more pressing when religion focuses exclusively on the afterlife in the immaterial and eternal world to come, and neglects the well-being of the material and temporal Universe. -------------- Zgłoszono: 30/08/2020. Zrecenzowano: 07/10/2020. Zaakceptowano do publikacji: 12/11/2020